Investigations on the Lewis-acids-catalysed electrophilic aromatic substitution reactions of thionyl chloride and selenyl chloride, the substituent effects, and the reaction mechanisms. (1st December 2013) - Sun, Xiaoping; Haas, David; McWilliams, Samantha; Smith, Benjamin; Leaptrot, Katrina
The previously established aluminium-chloride-(AlCl3)-catalysed electrophilic aromatic substitution (EAS) of benzene (PhH) with thionyl chloride (SOCl2) has been extended to toluene (PhCH3), chlorobenzene (PhCl), and phenol (PhOH). –CH3 was found to be mainly a para-director with a minor ortho-directing effect on the EAS reactions giving diaryl sulfoxides (Ar2SO). –Cl was found to be exclusively a para-director for formation of Ar2SO. All the –CH3, –Cl, and –OH groups were shown to be exclusive para-directors for formation of diaryl sulfides (Ar2S) from the EAS reactions. Although the reactions of PhH and PhCH3 with SOCl2 in the presence of AlCl3 gave the major Ar2SO and minor Ar2S at ambient temperature, the phenol (PhOH) reaction was shown to give only the reduced sulfide (p-HOC6H4)2S with no sulfoxide (p-HOC6H4)2SO formed. The mixed diaryl sulfoxides ArSOAr' (Ar, Ar'=C6H5, p-CH3C6H4; C6H5, o-CH3C6H4; and C6H5, p-ClC6H4) were produced in the AlCl3-catalysed reactions of SOCl2 with molar 1:1 PhH–PhX mixtures (X=CH3 and Cl). Efforts to enhance the yield of S-aryl arenesulfonothioates ArSO2SAr (Ar=Ph, p-CH3C6H4, and p-ClC6H4) from the AlCl3-catalysed EAS reactions of SOCl2 were made, showing that decreasing the molar ratios of ArH/SOCl2 or lowering the temperature resulted in an increase in the product yield. A detailed mechanism has been proposed to account for the formation of ArSO2SAr. The Lewis-acid-MCl3-(M=Al and Fe)-catalysed EAS reactions of PhH with selenyl chloride (SeOCl2) were demonstrated to give the reduced diphenyl selenide (Ph2Se) and diphenyl diselenide (PhSeSePh) via novel auto-redox processes in selenium of the key EAS intermediates.